Targeting ferroptosis reveals a new strategy for breast cancer treatment: a bibliometric study - Junlin Liu; Rong Tang; Jie Zheng; Ke Luo (Discover Oncology)
Abstract Background Studies exploring the role of ferroptosis in the pathogenesis of breast cancer have proliferated over the past decade, especially in 2023, with a staggering 217 publications in related studies. However, there are still significant gaps in comprehensive scientometric analysis and mapping of scientific studies, especially in terms of temporal and study area tracking, principal investigators, and the emergence of new hotspots. Objective This study aims to summarize the role of ferroptosis in the development of breast cancer and the latest research results on the ferroptosis-targeted treatment of breast cancer and to use bibliometric methods to draw a visual map to explore future research trends. Methods On May 11, 2024, this study updated the research progress related to ferroptosis and breast cancer over the past 11 years by retrieving data from January 1, 2014, to May 1, 2024, from the Web of Science database. In this research, many scientific analysis software including VOSviewer, chorddiag R Language Pack, Scimago Graphica, Citespace 6.3.R1, Cluster Profiler, enrichplot, ggplot2 R Language Pack, Cytoscape, and STRING online platform are used to make in-depth scientific analysis and visualization of the measurement results. Results Statistical analysis of these data showed that China accounted for 74.43% of the total publications, highlighting China’s dominant role in research on the relationship between ferroptosis and breast cancer. Several research institutions, including Sun Yat-sen University, Zhejiang University, and Shanghai Jiao Tong University, have achieved impressive results. Efferth, Thomas is the most prominent author in this field and has the highest number of publications in the subfield of oncology. This study clearly shows that ferroptosis plays a crucial role in the development of triple-negative breast cancer, hepatocellular carcinoma, glioma, leukemia, mitochondrial disease, lymphoma, bladder tumors, lung adenocarcinoma, and esophageal tumors. Conclusion This study provides a comprehensive bibliometric evaluation that deepens our understanding of the role of ferroptosis in the pathogenesis of breast cancer and the current status of targeting ferroptosis for treating breast cancer. Thus, it helps researchers in related fields explore new research directions by comprehensively extracting important information and research hotspots.